THE IMPLEMENTATION OF LOCAL WISDOM SIRI’NA PACCE AS AN EFFORT OF CORRUPTION ERADICATION IN INDONESIA - Muh. Afif Mahfud (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Corruption is one of development obstacle in developing countries include Indonesia. One of corruption factors is morality problem. To tackle this problem, the way can be used is implementation of siri’na pacce as a local wisdom. In this research, there are two issues namely first, how is the reality of corruption crime in Indonesia and second, how is the implementation of siri’na pacce as an effort to eradicate corruption in Indonesia. This is a normative research. Data is collected through literature research, analyzed qualitatively and depicted descriptively. Based on analysis, it can be concluded that corruption in Indonesia has been classified as an extra ordinary crime. One of the causes is number of state economical detriment because of corruption. Based on Corruption Eradication Commission data, number of state detriment because of corruption in 2014 is 5.9 Trillion Rupiahs. Corruption happen in executive, legislative and judicative sector. One of the ways used to eradicate corruption is implementation of local wisdom namely siri’na pacce. Siri’na pacce culture contains honest, social solidarity and obedience to regulation. The value of siri’na pacce must be implemented by people and government official. The purpose of siri’na pacce local wisdom implementation by people is to optimize social crime prevention in corruption eradication Key words :morality problem, corruption eradication, siri’na pacce